How best to use and evaluate Patient Information Leaflets given during a consultation: a systematic review of literature reviews. (26th September 2016) - Sustersic, Mélanie; Gauchet, Aurélie; Foote, Alison; Bosson, Jean‐Luc
Abstract: Background: In the past, several authors have attempted to review randomized clinical trials (RCT) evaluating the impact of Patient Information Leaflets (PILs) used during a consultation and draw some general conclusions. However, this proved difficult because the clinical situations, size and quality of RCTs were too heterogeneous to pool relevant data. Objective: To overcome this 30‐year stalemate, we performed a review of reviews and propose general recommendations and suggestions for improving the quality of PILs, how to use them and methods for evaluating them. Methodology: We searched five databases for reviews, systematic reviews and meta‐analyses describing PILs. We drew general and condition‐linked conclusions concerning the impact of PILs. Checklists summarize criteria for quality PILs, and ways of using and evaluating them. Results: Of 986 articles found, 24 reviews were pertinent; the five oldest considered the impact of PILs irrespective of the condition the patient consulted for; the 19 more recent ones mostly addressed precise clinical situations. Discussion: Whatever the clinical situation, PILs improve patients' knowledge and satisfaction. For acute conditions, in the short‐term PILs also improve adherence to treatment. For chronic diseases, invasive procedures or screening situations, their impact on adherence varies depending on the context, how the PILs are given and the invasiveness of the intervention. Conclusion: PILs are considered to be very useful, especially for acute conditions where the patient is the first to suffer from lack of information. We propose checklists for writing, designing, using and evaluating PILs in RCTs to enable comparisons between different studies.